Morphology and histochemistry of glandular trichomes in Hyptis villosa Pohl ex Benth. (Lamiaceae) and differential labeling of cytoskeletal elements - Santos Tozin, Luiz Ricardo dos [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Soc Botanica Brasil, 2017)
Lamiaceae contains many species known for their aromatic properties that are produced by the production of essential oils in glandular trichomes. Hyptis is one of the most common genera of Lamiaceae in the Brazilian flora, and includes several species with medicinal value. However, studies on the morphology and functioning of their glandular trichomes are lacking. We analyzed the morphology, histochemistry and ultrastructure of the glandular trichomes in leaves of H. villosa, emphasizing the differential distribution of actin filaments and microtubules in cells secreting hydrophilic and lipophilic compounds. Four morphotypes of glandular trichomes were identified. Total lipid, terpenes, alkaloids, phenolic compounds, proteins and polysaccharides were histochemically detected in all morphotyes. This evidences the mixed nature of the secretions of this species, although there are differences in the prevalence of lipophilic and hydrophilic components among the glandular morphotypes and among the cells of the same trichome. The actin microfilaments are more abundant in cells that secrete mainly hydrophilic compounds, and microtubules predominate in cells that secrete lipophilic compounds. Our results corroborate the correlation between the glandular morphotype and the composition of the secretion produced, with a differential distribution of the cytoskeletal elements according to the prevalence of either hydrophilic or lipophilic substances.
Keywords: actin microfilaments; cytoskeleton; glandular hairs; microtubules; ultrastructure